Short-Term Changes in the Ca(2+)-Exocytosis Relationship during Repetitive Pulse Protocols in Bovine Adrenal Chromaffin Cells - Engisch, Kathrin L. (J Neurosci, 1997)
Stimulus-secretion coupling was monitored with capacitance detection in bovine chromaffin cells recorded in perforated patch mode and stimulated with trains of depolarizing pulses. A subset of stimulus trains evoked a response with a Ca(2+)-exocytosis relationship identical to that obtained for single depolarizing pulses (Engisch and Nowycky, 1996). Other trains evoked responses with enhanced or diminished Ca(2+) efficacy relative to this input–output function. The probability of obtaining a particular Ca(2+)-exocytosis relationship was correlated with the amount of Ca(2+) entry per pulse, such that shorter pulses or smaller currents were associated with the greatest efficacy, and longer pulses and larger currents with the lowest efficacy. Apparent enhancements in Ca(2+) efficacy were not caused by residual Ca(2+) summing between pulses, because decreasing the interval between pulses usually reduced efficacy in the same cell; conversely, increasing the interval between pulses did not prevent an enhanced Ca(2+)-exocytosis relationship. Apparent decreases in Ca(2+) efficacy were not caused by depletion of an available pool of release-ready vesicles, because an equivalent amount of total Ca(2+)entry during a single long depolarizing pulse usually evoked a much larger secretory response in the same cell. Finally, there were no striking differences in global Ca(2+) levels monitored with the fluorescent indicator Fura Red that could account for apparent changes in Ca(2+) efficacy during repetitive stimulus protocols. It appears that in chromaffin cells, the Ca(2+)-exocytosis relationship is subject to activity-dependent changes during a stimulus train and can be modulated up or down from a basal state accessed by single pulse stimulations.